Effect of genistein on the gene and protein expressions of CXCL–12 and EGR–1 in the rat ovary - Zhang, Tao; Chi, Xiao‐Xing; Kong, Fan‐Xiu; Chu, Xiao‐Li (Journal of animal physiology and animal nutrition, 2021)
The effect of genistein (GEN) on the gene expression level of stromal cell‐derived factor‐1/CXCL‐12 and early growth response gene‐1 was studied in ovarian tissue of young and initially ageing (early stages in the ageing process) female rats. Forty, young female Sprague Dawley (SD) rats of 2–3 months old (200 ±20 g) and forty, initially ageing female SD rats of 10–12 months (490 ± 20 g) old were selected. According to the weight, rats were divided into control group, low‐dose group (L), medium‐dose group (M) and a high‐dose group (H) and were given 15, 30 and 60 mg/kg GEN respectively. The positive control (Oestrogen) group was given 0.5 mg/kg diethylstilbestrol. The treatment lasted for 30 days. The mRNA expression of C‐X‐C motif chemokine ligand 12 (CXCL‐12) and early growth response factor‐1 (EGR‐1) was measured by real‐time PCR, and protein expression of EGR‐1 was detected by Western blot. When compared to the negative control group (NC), the ovary/body weight ratio in the young rats decreased in the GEN group, but the difference was not significant. Similarly, compared with NC, the ovary/body weight ratio in the initially ageing rats also decreased with the increase in GEN concentration, but the decrease was significant in M and H groups (p < .01). The administration of GEN enhanced both the gene and protein expression levels of CXCL‐12 and EGR‐1 in the ovary. Pearson's correlation analysis showed a synergistic effect between CXCL‐12 and EGR‐1. Thus, we conclude that the effect of GEN on CXCL‐12 and EGR‐1 in the initially ageing group was obvious than that in the younger group.